Controls of vegetation structure and net primary production in restored grasslands. Issue 4 (3rd June 2014) - Munson, Seth M.; Lauenroth, William K.; Wilsey, Brian
Summary Vegetation structure and net primary production (NPP) are fundamental properties of ecosystems. Understanding how restoration practices following disturbance interact with environmental factors to control these properties can provide insight on how ecosystems recover and guide management efforts. We assessed the relative contribution of environmental and restoration factors in controlling vegetation structure, above‐ and below‐ground investment in production across a chronosequence of semi‐arid Conservation Reserve Program (CRP) fields recovering from dry land wheat cropping relative to undisturbed grassland. Importantly, we determined the role of plant diversity and how seeding either native or introduced perennial grasses influenced the recovery of vegetation properties. Plant basal cover increased with field age and was highest in CRP fields seeded with native perennial grasses. In contrast, fields seeded with introduced perennial grasses had tall‐growing plants with relatively low basal cover. These vegetation structural characteristics interacted with precipitation, but not soil characteristics, to influence above‐ground NPP (ANPP). Fields enrolled in the CRP for >7 years supported twice as much ANPP as undisturbed shortgrass steppe in the first wet year of the study, but all CRP fields converged on a common low amount of ANPP in the following dry year and invested less than half as much as the shortgrass steppe in below‐ground biomass. ANPP in CRP fields seeded with native perennial grasses for > 7 years was positively related to species richness, whereas ANPP in CRP fields seeded with introduced perennial grasses was controlled more by dominant species. Synthesis and applications. Seeding with introduced, instead of native, perennial grasses had a strong direct influence on vegetation structure, including species richness, which indirectly affected NPP through time. However, the effects of restoring either native or introduced grasses on NPP were secondary to low water availability. Therefore, restoration strategies that maximize basal cover and below‐ground biomass, which promote water acquisition, may lead to high resilience in semi‐arid and arid regions.